Statistical analysis of air-conditioning and total load diversity in typical residential buildings - Naja Aqilah Hisham; Sheikh Ahmad Zaki Shaikh Salim; Aya Hagishima; Fitri Yakub; Hafizah Farhah Saipan Saipol (Institute of Advanced Engineering and Science, 2021)
Electricity consumption by air-conditioners in residential buildings significantly affects the electrical grid. The stability of the grid can be improved by a precise prediction of air-conditioning (AC) variations. Therefore, more information about the electricity usage patterns specifically on AC load is important. This paper aims to determine the consumption patterns of AC and total load through a field measurement of 20 dwellings located in Kuala Lumpur and Selangor. Next, correlation and clustering are employed to identify the relationship between outdoor temperature and AC electricity consumption. The results revealed 75% of the occupants use the AC almost every day for about five to six hours per day at the rates of 0.93 kWh/day during day time and 3.43 kWh/day during night time. The correlation coefficient between the total daily AC consumption and the mean daily outdoor temperature ranged from -0.1 to 0.48. The variation of electricity consumption with time shows that AC electricity consumption increases with the increase of usage time. Lastly, the clustering process of AC usage pattern based on outdoor temperature displayed the uncommon behaviour from dwellings whereby high AC electricity consumption was recorded at low outdoor temperature.